(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The study explores how metaphors, metonymy, phraseological units, and symbolic expressions are used in both languages to construct semantic depth. It compares the specific cultural and linguistic features of Uzbek and English that shape how images and symbols are formed. Particular attention is paid to the challenges of translation, such as semantic loss or misinterpretation of symbolic meanings across languages. The article aims to identify and analyze the functional capacity of these lexical units, revealing the national identity reflected through linguistic imagery.